Studies of root formation of micropropagated shoots in vitro and cuttings from light treated mother plants ex vitro - Hedman, Yvonne (2006)
The ornamental plant Aristolochia manshuriensis is difficult to propagate by cuttings and therefore a propagation method in vitro has been developed. However the published method has several limitations due to unpredictable and low rooting percentage as well as low survival rate. In this study several factors were investigated in order to improve rooting in vitro and survival ex vitro. To improve rooting the amount of cytokinin was reduced before rooting. Different types and levels of auxins and the use of riboflavin together with indole-acetic acid (IAA) were tested. In order to change the ratio between carbon and nitrogen, different concentrations of macro nutrients were used. Glutamine as the only nitrogen source was tested as well as different types of iron source. Addition of activated charcoal to the hormone free medium in combination with long or short exposure to auxin were used to improve both rooting and survival. In order to improve rooting of cuttings ex vitro, the mother plants were grown under different light regimes (20 and 200µmol m-2 s-1) and cuttings were treated with different type and concentrations of auxin with and without glucose. The rooting process for the cuttings taken ex vitro was very slow and good rooting was in some cases not obtained until after 34 weeks. After 9 weeks the highest rooting frequency was only 40%. The cuttings have a tendency to stay green during long time, even without callus or root formation. In some cases the shoot produced new leaves without any production of roots. Mother plants grown at 20 µmol m-2 s-1 were more vigorous and the cuttings from them had better rooting percent than from those grown under 200µmol m-2 s-1. The best rooting was 70% for cuttings treated with IAA at 500 mg/l after 34 weeks. In general the treatments with auxins and sugar gave the lowest rooting capacity. Rooting in vitro of microshoots resulted in more rapid rooting. After 3 weeks, on medium containing 1/3 of macro nutrients and IAA at 20 mg/l, 52% rooting was obtained. However these plantlets were not transferred to ex vitro. The most rapid in vitro rooting was obtained after 2 weeks using dipping in IBA solution at 250 mg/l for 30 minutes and then transferred to hormone free medium containing 10g/l activated charcoal resulting in 24% rooting. After planting in soil, 60% rooting was recorded after 13 weeks. Several months after the in vitro rooting experiments had been planted ex vitro there were explants thought to be dead but when examining them thoroughly callus was found growing from the root lump or new leaves and roots under the surface. Treatments resulting in high callus formation had lower rooting than treatments with less callus formation.